2019
DOI: 10.3390/f10020108
|View full text |Cite
|
Sign up to set email alerts
|

Iterative Models for Early Detection of Invasive Species across Spread Pathways

Abstract: Species distribution models can be used to direct early detection of invasive species, if they include proxies for invasion pathways. Due to the dynamic nature of invasion, these models violate assumptions of stationarity across space and time. To compensate for issues of stationarity, we iteratively update regionalized species distribution models annually for European gypsy moth (Lymantria dispar dispar) to target early detection surveys for the USDA APHIS gypsy moth program. We defined regions based on the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 112 publications
0
20
0
Order By: Relevance
“…For example, as remote sensing technology improves spatial resolution and coverage, these new environmental data can be incorporated into the environmental variable library to provide additional predictive power that has been shown to effectively map invasive spices populations in localized examples [9]. As shown with gypsy moth, operational iterative modeling can improve models over time and lead to better informed management actions [15]. Our models represent the first iteration of these predictions.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…For example, as remote sensing technology improves spatial resolution and coverage, these new environmental data can be incorporated into the environmental variable library to provide additional predictive power that has been shown to effectively map invasive spices populations in localized examples [9]. As shown with gypsy moth, operational iterative modeling can improve models over time and lead to better informed management actions [15]. Our models represent the first iteration of these predictions.…”
Section: Plos Onementioning
confidence: 99%
“…Making the most credible SDM takes considerable effort and often requires collecting information that is not readily available (e.g., on species absence and detection probability), while a fully automated process using a standard set of existing information may produce many models quickly but has less credibility. Iterative modeling, the incremental improvement of SDMs based on added information and modified modeling processes over time, provides a way to minimize the tradeoffs between quality and quantity of models created and to objectively demonstrate improvement of models with the use of additional information, including new data, expert review, and field validation [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome issues related to uncertainty and stationarity, Cook et al [1] used iterative distribution models to direct early detection of invasive European gypsy moth (Lymantria dispar dispar L.) in the United States. They concluded that incorporating human-assisted pathway predictors can greatly improve early detection of invasive species.…”
Section: Contributions In Briefmentioning
confidence: 99%
“…The computations that constitute target analysis are largely built on existing information and use statistical sampling theory (Russell et al 2017;Berec et al 2015;Hoffman et al 2016; US Forest Service n.d.; http:// www.landscapetoolbox.org, accessed 24 September 2018). Modeling helps extend estimates about the invasive species in space and/or time (Cook et al 2019;Wang et al 2014). Mapping is used to consider important geospatial information, jurisdictional boundaries, and logistical aspects of surveillance strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Department of Agriculture On an annual basis, USDA's Animal and Plant Health Inspection Service (APHIS) has been using aspects of target analyses to forecast the likelihood of detecting European gypsy moth (Lymantria dispar dispar) outside of the existing federal quarantine area. Because pathways for spread differ across space (from natural spread over relatively short distances to human-assisted spread over long distances), the gypsy moth model is regionalized to capture these different pathways (Cook et al 2019). The resulting model output is used to guide sampling, directing more effort to high-probability locations (USDA 2014).…”
Section: Introductionmentioning
confidence: 99%